INFORMATIONAL DYNAMICS IN RESISTANCE AGAINST THE DESTRUCTION OF SOCIOBIODIVERSITY IN THE AMAZON: THE ROLE OF ONLINE MEDIA AND CYBERACTIVISM - Issberner, Liz Rejane; Dias, Julia (AoIR Selected Papers of Internet Research, 2026)
The Brazilian Amazon is the site of several conflicts involving threats to its biodiversity, the traditional populations that live there. In the region, a harmful combination of disparities in power, knowledge and access to information also prevails, in addition to divergent views on how to deal with such conflicts. The ongoing research investigates the information dynamics in communities that have resisted for years the invasion of neo-extractivist projects and the threats. The particular focus in on the role of new digital media specialized in disseminating information about threats to sociobiodiversity and violence to defender in the Amazon, giving them global visibility. The research methodology includes mapping media vehicles and other organizations specialized in covering conflicts in the Amazon in Brazil, the application of structured questionnaires to collaborators and activists, the conduct of in-depth interviews and a field study in two cities in the state of Pará. More than 100 news outlets, NGOs and associations of indigenous communicators that work with this mission have already been identified. The idea is to track the entire path of information, from its origin to its dissemination, including the production of information and verification of content.